El impacto de los factores críticos de éxito en la implementación de sistemas integrados de ERP - Maldonado, Miguel (2008)
Although is a recent topic, the analysis of the success of the integrated systems implementation of the enterprise resource planning (erp) is a topic that has a lot of relevance for the information technology (it) community. However, as a result of this novelty, most of the existent investigation is limited to qualitative methodologies or descriptive studies oriented to big companies or corporations mainly. This investigation presents a model that seeks to reveal the determining factors of the success of erp implementation in a small and medium Latin American company. The validation of this empiric model allowed to verify significant relationships between training and it abilities in the company and the success of the implementation, measured by the time required for this one. It was also verified the impact of this time over the perception of the companies global satisfaction with the erp implementation. The investigation concludes with recommendations for its application and also suggests additional potential areas of investigation inspired by an amazing collateral result obtained